Kudzula Kadfiz from the Title of “Yabgu” To “King of Kings” (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
It is known from history that the political importance of a country is determined by the honorary title of the ruler or the honorary status of the person who leads this country, in addition to various factors. These titles are inherited from the ruler to his son or acquired during the struggle for power with other equal claimants to the throne. In the process of the expansion of the state and further growth of its power, the personality of the first ruler who had a simple name (title) and his title of rulership grew accordingly and became deified. In some cases, they went as far as considering the rulers of the state as relatives of the gods, for example, the Egyptians called the ruler "son of Ra", in China they were called "son of God" or "child of heaven", in Hindus they were called "devaputra, (son of God), and in Bactrians "bagopoiro" (son of God). and accordingly, in Assyria, the kings with the titles of "Sar-sarani" and "Lugal" further deified themselves[1].[1] Ртвеладзе Э.В. История государственности Узбекистана.Ташкент.Ўзбекистон нашриёти.2009.330-б.